Comparative analysis of indwelling time and complications of mid-line catheters in different punctured veins of neonates - Yang, Lijuan; Wang, Yixin; Luo, Song; Tao, Yanju; Shi, Xinxin; Xu, Wenda; Li, Yanling; Sun, Caixia; Lei, Tingting; Xu, Bing (Frontiers in Pediatrics, 2025)
ObjectiveWe aims to evaluate the effects and complications associated with mid-line catheters inserted via different puncture veins in neonates, ultimately providing a foundation for selecting the most suitable puncture site for catheterization in clinical neonatal practice.MethodsA retrospective data analysis was conducted, involving 244 neonates with indwelling mid-line catheters who were admitted to a Class III Grade A general hospital in Anhui Province between August 2020 and December 2023. The study compared catheter indwelling duration, the incidence of catheter-related complications, and the first puncture success among neonates with catheterization through various veins.ResultsThe analysis revealed a statistically significant difference in indwelling duration across different puncture veins (H = 28.65, P < 0.001). Specifically, significant differences were observed in the indwelling duration between the median cubital vein, axillary vein, and superficial temporal vein (adj. P < 0.05), whereas no significant differences were found among the other puncture sites (adj. P > 0.05). A statistically significant variation in catheter complications was observed among different puncture veins (P < 0.001). Specifically, the incidence of complications was lower in the median cubital and axillary veins compared to other puncture sites, with these differences reaching statistical significance (P < 0.05). Furthermore, the basilic vein exhibited a lower incidence of complications than the cephalic vein, superficial temporal vein, and great saphenous vein, with the difference being statistically significant only when compared to the great saphenous vein (P < 0.05). Additionally, no statistically significant difference was found in the success rate of single puncture among the various puncture veins (P > 0.05). However, the one-time successful catheter insertion rate was significantly higher for the median cubital and axillary veins compared to other veins (P < 0.05), while no statistically significant differences were observed among the remaining veins.ConclusionThe insertion of mid-line catheters into the axillary vein and the median cubital vein has been shown to extend catheter indwelling time, enhance the ease of catheter insertion, and decrease the incidence of complications. Consequently, it is advisable to prioritize the axillary vein and median cubital vein for the insertion of mid-to-long catheters in neonates.